ASSESSING INTERNET LITERACY AMONG STUDENTS IN NPEO 2022: AN ANALYSIS OF KNOWLEDGE AND SKILLS AT AMBON STATE POLYTECHNIC - Sari, Hindri Febri Ana; Nusi, Ahmad; Persulessy, Sylvia Irene; Hahury, Jessy Juniu (TELL - US JOURNAL, 2023)
This study aims to examine the internet literacy level of students in the National Polytechnic English Olympic (NPEO) selection at Ambon State Polytechnic 2022. The researchers are interested in understanding the internet literacy of 30 students focusing on the use of search engines, social media, email, and downloading. The research employed a descriptive qualitative approach and utilized questionnaires to collect data. The data is then analyzed using the capability Maturity Model Theory. The results revealed that the internet literacy level of students in the National Polytechnic English Olympic (NPEO) at Ambon State Polytechnic 2022 was at level 2 with 50 %. This final result related to the self-rating internet proficiency with 48% (at intermediate level), internet usage and internet capability with 86 % (at good category), and knowledge test with 60 % (at Middle level). The results also elucidated several factors that affected internet literacy among the students, such as gender, age, and internet usage experience.